Energy Consumption Pattern of a Decentralized Community in Oyo State, Nigeria - Odesola, Isaac; Awoyemi Omotola, Omotola; Folorunso, Amos (Journal of Advanced Mechanical Engineering Applications, 2020)
Energy is required in the manufacture of various products and in the movement of goods and services within and outside a country. Energy consumption patterns, which consist of energy sources, quantities and the demographics of the consumers, help in drawing a clearer picture of the economic situation of the location. This work involves a survey of the household energy consumption pattern carried out in a decentralised community. As established from research, there is a direct correlation between economic development and energy consumption. It is therefore imperative to study the energy usage of rural areas to help decision makers tackle their energy problems. Energy conversion methods were employed for the conversion of the raw data collected into energy units to determine the quantities of energy consumed in various sectors at the Alagbaa community in Akanran, Ona Ara Local Government Area, Oyo State, Nigeria. The survey covered a heterogeneous population of different income groups and social groups and studies were carried out on the total and average quantities of energy consumed in the domestic, transportation and agricultural sectors. Home electrification accounted for 37% of the total energy used by a household while transportation, cooking and agriculture accounted for 35%, 13% and 15% respectively. From the study, it was found that economic inequality is also displayed in the choice of energy sources with higher deviation found in the total amount in the use of energy. It was also found that the least conventional source of energy, firewood, showed higher deviation. It also revealed that 50% of the energy used was channelled to non-economic activities.